Multimodal imaging and genetic characteristics of Chinese patients with USH2A‐associated nonsyndromic retinitis pigmentosa. Issue 11 (6th September 2020) - Chen, Chong; Sun, Qiao; Gu, Mingmin; Qian, Tianwei; Luo, Dawei; Liu, Kun; Xu, Xun; Yu, Suqin
Abstract: Background: To determine the clinical characteristics and molecular genetic background responsible for USH2A mutations associated with nonsyndromic retinitis pigmentosa (RP) in five Chinese families, a retrospective cross‐sectional study was performed. Methods: Data on detailed history and comprehensive ophthalmological examinations were extracted from medical charts. Genomic DNA was sequenced by whole‐exome sequencing. The pathogenicity predictions were evaluated by in silico analysis. The structural modeling of the wide‐type and mutant USH2A proteins was displayed based on the I‐Tasser software. Results: The ultra‐wide‐field fundus imaging showed a distinctive pattern of hyperautofluorescence in the parafoveal ring with macular sparing. Ten USH2A variants were detected, including seven missense mutations, two splicing mutations, and one insertion mutation. Six of these variants have already been reported, and the remaining four were novel. Of the de novo mutations, the p.C931Y and p.G4489S mutations were predicted to be deleterious or probably damaging; the p.M4853V mutation was predicted to be neutral or benign; and the IVS22+3A>G mutation was a splicing mutation that could influence mRNA splicing and affect the formation of the hairpin structure of the USH2A protein. Conclusions: Our data further confirm that USH2A protein plays a pivotal role in the maintenance of photoreceptors and expand the spectrum of USH2A mutations that are associated with nonsyndromic RP in Chinese patients. Abstract : This study identified novel mutations of the USH2A gene using a whole‐exome sequencing approach in nonsyndromic RP patients. RP patients with USH2A mutations have a distinctive pattern in ultra‐wide‐field fundus autofluorescence.